Synthesis, characterisation and spectroscopic studies of diazine-N-oxide complexes of iron(II) towards the development of sensors - Mpiti, Unako Bongani (Rhodes University, Faculty of Science, Department of Chemistry, 2019)
The characteristic magnetic and spectroscopic features associated with the red monomeric or dimeric, and polymeric pyrazine-N-oxide (PyzNO) iron(II) perchlorate complexes; Fen(Î¼1,1-pyzNO)2n-2(pyzNO)3n+2(ClO4)2n (n = {1, 2}*, and the novel compound {Fe(Î¼-pyzNO-ÎºN,ÎºO)n-1(pyzNO-ÎºN)2(pyzNO-ÎºO)2}n(ClO4)2n" , respectively, were investigated. These properties are altered substantially when the complexes are hydrated; for instance, by atmospheric exposure. The resulting species; Fe(pyzNO)5(H2O)3(ClO4)2* and [Fe(pyzNO-ÎºN)4(H2O)2](ClO4)2.2H2O" , which have different hues of a bright yellow colour, were found to exhibit strong paramagnetism, in contrast to their anhydrous precursors, which are 'EPR silent'. A low spin â†’ high spin crossover (LSâ†’HS, SCO) transition was therefore proposed to occur as the complexes become hydrated by atmospheric moisture. The redâ†’yellow colour change is reversible, and dehydration of the yellow species by heating regenerates the red variant, a feature which lends itself to the potential applicability of the system as a sensor. Further emphasis on this potential derives from the fact that the hydration/dehydration process, and its accompanying physical changes, appears reversible even after many such treatments. It became of interest, then, to determine if these changes were limited to water-exposed samples, or if they occurred under more diverse solvent atmospheres. The reversibility of such exposure on the structure of the novel polynuclear complex was therefore investigated. In general, it was found that there occurred a strong solvent-complex association for the more polar solvents. Redâ†’yellow, LSâ†’HS events were seen when the complex was exposed to the vapours of p-dioxane, acetaldehyde and formaldehyde, and to a lesser extent, to that of methanol. In each case, significant structural changes were seen, as evidenced be comparative XRPD and thermo-analytical studies. Some of these changes have however been ascribed to the effects of partial dissolution upon extended exposure of the complex to the associated media. Exposure to less polar solvent atmospheres, such as those of cyclohexane, toluene, diethyl ether, etc., showed some signs of mild solvent surface adhesion, but were unaccompanied by discernible magnetic and colour changes. Another novel complex was produced during attempts to synthesize the PyzNO complexes from a mixture of a 2,2'-dimethoxypropane (DMP) and ethanol (1:1, v/v), rather than the methanol/DMP mixture which had been alternately used. The formula of the resulting complex is Fe(pyzNO)6(ClO4)2.3EtOH*. This EPR inactive product was orange in colour, and transformed into a bright yellow, strongly paramagnetic species upon atmospheric exposure. Further solvent studies showed that this species interacted significantly with all solvents tested, but generally more strongly with increasing solvent polarity. Orangeâ†’yellow colour changes occurred in environments saturated with p-dioxane, acetaldehyde and formaldehyde vapours. The DMSO-exposed sample transformed to dark red, due to suspected PyzNO substitution by the solvent. The redâ†’yellow and orangeâ†’yellow colour changes were ascribed to the formal substitution of O-coordinated PyzNO (Î¼-PyzNO in the polymeric complex) by the incoming solvent. The resulting structural and geometric changes stimulated a redistribution of d electrons among the new constituent molecular orbitals of altered energy and symmetry. Therefore, although the colour changes were not conventionally solvatochromic - in that the original structure was lost on exposure "“ data suggested that it was the coordination of species of higher donor strength that produced the observed bathochromic shifts. A novel 4,4'-bipyridine-N-oxide Fe(II) perchlorate complex, Fe2(bipyNO)5(ClO4)4.6MeOH" , was also produced, primarily for physicochemical comparison with the PyzNO complexes. No colour or magnetic changes were seen on atmospheric exposure. The original complex was observed to be inherently paramagnetic, and no SCO events occurred upon solvent exposure. Despite this, thermal analyses showed that the complex did exhibit the strong uptake of polar solvents in general, but particularly with acetaldehyde. Significant structural changes upon exposure were limited to surface phenomena, with the exception of the acetaldehyde-exposed sample.
Keywords: Diazines; Ligands; Iron